Estradas de ferro e ensino industrial: um estudo de caso - Medeiros, Marluce (1980)
This paper studies the history and work of the Centro Ferroviário de Ensino e Seleção Profissional de são Paulo created in 1934, in a joint venture, by the railroad system and the State Government of são Paulo . The Center emerged precisely in the são Paulo State due to the expansion needs of são Paulo's coffee economy, which required rapid, cheap and long distance transportation . Another factor that propiciated the creation there of the Center was the wide acceptance throughout the são Paulo State of the ideas of Scientific Management of Work, with its aims the labor-force's productivity . Such ideas , industry, met with great success , even growing introduction of Personnel Selection and Human o f i n c re a si n g as applied to towards the Re 1 at i on s. Services in our industry , regarded as valuable ways of taking advantage of the 'human factor' . The Instituto de Or ganização Racional do Trabalho de são Paulo (IOORTl had a proerninent place in the spreading of such theories and practices to technical education Crailroad schoolsl . Marking this influence was their learning 'methodical series ' and also their application of psychometrics to personnel selection as well as to the selection of candidates to voc ational schools. These procedures were initially used at the Liceu de Artes e Ofícios de são Paulo, and later on at Estrada de Ferro Sorocabana. During its eleven years of functioning the Centro Ferroviário de Ensino e Seleção são Paulo prepareded qualified labor-force Profissional de for são Paulo railroad industry and also for that of other States, making good use of specia1ly p1anned 'methodes of learning' and also of their results in vocationa1 technica1 qua1ification of workers. It a1so p1ayed a decisive role in the founda tion of the SENAI, an agency to which the Center was in corporated in 1945, under the name of Transport Division . I~ fact, however it most1y offered qua1ified personnel , special teaching methodes, and idRology.